Workplace Stress of Special School Teachers at Three Schools in Bali Province - Prawira Natha Kusuma, Made Adhyatma; Biomi, Agnes Ayu; Wulandari Artha, Luh Putu (Preventia: The Indonesian Journal of Public Health, 2023)
Workplace stress is often seen as a threat or a problem that comes from the work environment. Stress is a feeling resulting from the interaction between the individual and the work environment. Work stress can happen to anyone at any time, including special school teachers. This research aims to describe the workplace stress of special school teachers at three schools in the Bali Province. This research was conducted in October-December 2022. Researcher used quantitative research method with cross-sectional design and descriptive approach. Data collection is carried out using the Copenhagen Psychosocial Questionnaire-III and the Occupational Diagnosis Survey from the Ministry of Manpower Indonesia. The sample of this research was 95 participants. Researcher use total sampling technique. The results showed that 52.63 percent of respondent experience workplace stress in the moderate categories and 44.21 percent in the mild categories. Based on the diagnosis to what extent work conditions are a source of stress, 14.74 percent of respondents are moderately stressed due to ambiguity of roles, 15.74 percent are due to role conflict, 37.89 percent are due to quantitative overload, 57.89 percent are due to qualitative overload, 13.68 percent are due to career development, and 62.11 percent are due to responsibility towards others.